2015
DOI: 10.1007/s10608-015-9737-x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Single-Session Positive Reappraisal, Cognitive Restructuring and Supportive Counselling for Older Adults with Type 2 Diabetes

Abstract: This study compared a single-session intervention of positive reappraisal to cognitive restructuring and supportive counselling to examine whether a brief positive reappraisal intervention could significantly increase positive reappraisal coping and positive emotion and lead to reductions in anxiety and depression. Inclusion criteria were: aged 60 years or older, diagnosed with type 2 diabetes, cognitively intact, and English language proficiency. 81 participants were randomly allocated to a condition and self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Recent researchers have suggested that personality traits such as neuroticism and optimism are mutable and change can be achieved through psychosocial interventions such as Cognitive‐Behaviour Therapy (CBT; e.g., Glinski & Page, ; Seligman, ). Similarly, CBT has also been found to help modify cognitive appraisals (e.g., Chalk, ; Nowlan, Wuthrich, Rapee, Kinsella, & Barker, ). Based on the model, CBT should target modification of threat appraisal and strategies to increase challenge and social support appraisals to foster well‐being and reduce ill‐being.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researchers have suggested that personality traits such as neuroticism and optimism are mutable and change can be achieved through psychosocial interventions such as Cognitive‐Behaviour Therapy (CBT; e.g., Glinski & Page, ; Seligman, ). Similarly, CBT has also been found to help modify cognitive appraisals (e.g., Chalk, ; Nowlan, Wuthrich, Rapee, Kinsella, & Barker, ). Based on the model, CBT should target modification of threat appraisal and strategies to increase challenge and social support appraisals to foster well‐being and reduce ill‐being.…”
Section: Discussionmentioning
confidence: 99%
“…Of the five RCTs, four (80%) adequately described their randomization sequence (Bond et al, 2010 -Reid et al, 2018), blinding of study per-sonnel was not described; all were rated as either high or unclear. For the attrition bias assessment, only two studies (40%) were free from frequent missing data (Nowlan et al, 2015;Weiss et al, 2015). In the three remaining studies (Bond et al, 2010;Taveira et al, 2011;Markle-Reid et al, 2015, 2018, no information was provided concerning the attrition rate or reasons for missing data.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…RCTs(Bond et al, 2010;Taveira et al, 2011;Nowlan et al, 2015;Weiss et al, 2015;Markle- Reid et al, 2018) were included in a qualitative literature synthesis and a description of changes in depressive symptoms and blood glucose controls.…”
mentioning
confidence: 99%
See 2 more Smart Citations